Correlates and contributors of reproductive coercion across the socioecological framework among intimate partner violence survivors in Nairobi, Kenya - Wood, Shannon N. (Journal of family violence, 2023)
Purpose: Reproductive coercion (RC) is a type of intimate partner violence that involves interference in contraceptive and reproductive decisions. A multi-methods design explored correlates (quantitative) and contributors (qualitative) of partner-perpetrated RC across the socioecological framework among intimate partner violence survivors (IPV) in Nairobi, Kenya. Methods: Quantitative analyses utilize baseline data from the myPlan Kenya trial (n=327). Multivariable Poisson regression examined the association between postulated correlates and overall RC (range: 0-9), and sub-types of pregnancy coercion (range: 0-5) and condom manipulation (range: 0-4). In-depth interviews (IDIs; n=30) conducted at three-month follow-up among women indicating RC experience at baseline explored women’s perceived contributors to RC via inductive thematic analysis. Results: Within the past three months, over 80% of IPV survivors experienced any RC, and IPV survivors experienced 3.8 RC behaviors on average. Factors associated with overall RC included not wanting their last child at all (aIRR =1.28; p=0.009), partner’s concurrent partnership (aIRR=1.33; p<0.001), and inconvenient contraceptive method use (aIRR=1.36; p=0.01), whereas increased couple communication was protective against RC (aIRR=0.96; p<0.001). IDIs revealed potential contributors to RC, including partner’s desire for children; partner fear of contraceptive side effects; cultural norms surrounding family planning use within marriage; decision-making power disparities reinforced by economics; partner’s fear of abandonment; and presence of children from previous relationships. Conclusions: Results indicate individual- and couple-level characteristics are crucial for understanding RC for Nairobi’s IPV survivors. Knowledge of RC risk factors can assist practitioners in mitigating against reproductive interference, and ensuring women are using contraceptive methods most suited to their circumstances and aligned with their reproductive preferences.